Praktik Penyelesaian Sengketa Perbankan Syariah Di Pengadilan Agama Kota Kediri - Farihatul Lailiyah; Trinah Asi Islami (Universitas Merdeka Madiun, 2022)
This study aims to analyze the practice of sharia banking dispute resolution at the Kediri City Religious Court, to review the obstacles experienced by the Kediri City Religious Court in resolving sharia banking disputes, to examine the efforts that must be made by the parties towards the settlement of sharia banking disputes in the courts. Religion of the City of Kediri in order to create legal goals. This study uses field research and literature, there are two sources of data in this study, namely primary data sources and secondary data, after combining the data exposure using deductive, descriptive and inductive methods. The results of this study explain that the settlement of sharia banking disputes at the Religious Courts of the City of Kediri is still done manually and of course there are obstacles faced by the religious courts of the city of Kediri, namely from justice seekers and third parties, so in this case to realize the legal objectives to make it more effective. effective and efficient is resolved by peaceful means or amicably using a mediator.